INVESTASI SWASTA SEKTOR PARIWISATA DAN PENYERAPAN TENAGA KERJA DI PROVINSI BALI (Sebuah Analisis Tipologi Daerah) - Setyadhi Mustika, Made Dwi (INPUT Jurnal Ekonomi dan Sosial; Vol. 1, No. 2 Februari 2009, 2012)
This paper discuss about private invesment of tourism sector and labour absorbtion in Bali Province for the year 2002-2005, which is analysed using tipologi area. The data used are secondary data, consisted of private invesment on tourism sector and labour absorbtion in 9 (nine) regencies/city in Bali Province. The data obtained from BKPMD of Bali Province, Labour Office of Bali Province, and BPS of Bali Province. The result of the research could be elaborated as follows. Badung Regency, Karangasem Regency, and Denpasar City are owning private invesment of tourism sector and labour absorbtion level higher than mean of Bali Province. Jembrana Regency and Bangli Regency are owning private invesment of tourism sector and labour absorbtion level lower than mean of Bali Province.
Keywords: private invesment, labour absorbtion, tipologi area